KONVERSI PROYEKSI PETA TEMATIK KAWASAN TAMAN NASIONAL GUNUNG HALIMUN KE DALAM FORMAT DERAJAT DESIMAL - Roemantyo, Roemantyo; Hartoko, B; Prawiroatmodjo, S; Maryanto, I; Widodo, R; Mulyono, B; Yamada, Y (BERITA BIOLOGI, 2001)
-